2017
DOI: 10.17113/ftb.55.04.17.5138
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Pancreatic Lipase by Polyphenols: A Kinetic, Fluorescence Spectroscopy and Molecular Docking Study

Abstract: The inhibitory activity and binding characteristics of caffeic acid, -coumaric acid, quercetin and capsaicin, four phenolic compounds found in hot pepper, against porcine pancreatic lipase activity were studied and compared to hot pepper extract. Quercetin was the strongest inhibitor (IC=(6.1±2.4) µM), followed by -coumaric acid ((170.2±20.6) µM) and caffeic acid ((401.5±32.1) µM), while capsaicin and a hot pepper extract had very low inhibitory activity. All polyphenolic compounds showed a mixed-type inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 42 publications
5
82
1
6
Order By: Relevance
“…Pancreatic lipase is involved predominantly with the breakdown of dietary lipids and their assimilation in the intestine; hence, pancreatic lipase inhibitors are used to prevent the absorption of fats in the diet, making them ideal for the management of obesity or overweight [35][36][37]. Previous reports have suggested that polyphenols such as caffeic acid, p-coumaric acid, quercetin, and capsaicin from hot peppers are good pancreatic lipase inhibitors [38]. The inhibitory activities of PP4 and PP6 indicate the importance of L. tetragona in the control of lipid deposition in the body and ultimately in the management of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic lipase is involved predominantly with the breakdown of dietary lipids and their assimilation in the intestine; hence, pancreatic lipase inhibitors are used to prevent the absorption of fats in the diet, making them ideal for the management of obesity or overweight [35][36][37]. Previous reports have suggested that polyphenols such as caffeic acid, p-coumaric acid, quercetin, and capsaicin from hot peppers are good pancreatic lipase inhibitors [38]. The inhibitory activities of PP4 and PP6 indicate the importance of L. tetragona in the control of lipid deposition in the body and ultimately in the management of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…La inhibición de la actividad de la enzima lipasa pancreática se realizó de acuerdo a Martinez-Gonzalez et al (2017a). La lipasa se disolvió en una disolución amortiguadora Tris 20 mM (pH = 7.2), a una concentración final de 2.0 mg/mL.…”
Section: Análisis De La Actividad Enzimática De Lipasa Pancreáticaunclassified
“…La disminución de su actividad enzimática por inhibidores reversibles, como los polifenoles, es objeto de estudio ya que podrían eliminar los efectos secundarios de un inhibidor no reversible (Sakulnarmrat y Konczak, 2012). Se ha reportado una actividad inhibitoria en valores de IC 50 (concentración del ligando a la cual se inhibe la mitad de la actividad enzimática), más eficiente para flavonoides como la quercetina, en comparación con ácidos fenólicos como el ácido caféico (Martinez-Gonzalez et al, 2017a). Extractos vegetales ricos en flavonoides como QUE han sido evaluados por su elevada actividad inhibitoria frente a lipasa (Sakulnarmrat y Konczak, 2012), pero no se les había asociado con su estructura.…”
Section: Introductionunclassified
“…This enzyme has been intensely studied because of its relation to anti– obesity treatments (5, 6). In addition to myricetin, some other flavonoids have been proposed to be lipase inhibitors, for example it has been shown that quercetin can bind to lipase near the active site (7). Many of these studies are based on molecular docking, where the flavonoids are considered soluble compounds and the interaction happens at the molecular level.…”
Section: Introductionmentioning
confidence: 99%